PENERAPAN TEKNIK BUTTERFLY HUG UNTUK MEREDAKAN KECEMASAN DALAM PEMBELAJARAN BAHASA INDONESIA PADA SISWA KELAS IX.8 DI SMP NEGERI 7 PALEMBANG - Novalia Novalia; Juaidah Agustina (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Anxiety is a common problem faced by students, especially at the secondary education level, and can interfere with concentration and learning ability. This study focuses on the application of the Butterfly Hug technique to relieve anxiety in grade IX students at SMP Negeri 7 Palembang. This technique, which involves hugging oneself, aims to improve social-emotional skills and create a conducive learning atmosphere. The research method used was descriptive qualitative, involving 36 students as subjects. The results showed that the application of the Butterfly Hug technique was effective in increasing students' sense of comfort, focus, and participation during learning. Students reported improvements in emotion management and material comprehension. Although there are challenges in its application, such as initial awkwardness, it is important for teachers to create a supportive environment. Overall, this technique has the potential to be integrated more widely in learning activities to support learners' emotional well-being.